Strategi Komunikasi Pemberdayaan Ekonomi Perempuan - Sari, Yunita; Handayani, Mediana; Nugroho, Eko (ABDI MOESTOPO: Jurnal Pengabdian Pada Masyarakat, 2026)
Women's economic empowerment is a crucial strategy for creating sustainable prosperity and socio-economic resilience in communities. This study aims to formulate an effective, inclusive, and participatory communication strategy to support the economic independence of women micro-entrepreneurs in the creative economy sector. The program was implemented using a descriptive qualitative approach through community needs mapping, experience-based training, and mentoring based on interpersonal communication, social media, and community networks. These activities involved field observations, focus group discussions, in-depth interviews, and participatory evaluation through reflection and case studies. The results indicate that increased communication literacy, strategic use of digital media, and the formation of a connected women's business community are indicators of real social transformation. Participants experienced increased self-confidence, innovation in product development, and the ability to establish business collaborations. This study confirms that a bottom-up communication strategy designed, adapted to the local cultural context and women's social dynamics, can be a sustainable social intervention. The novelty of this finding lies in the hybrid communication model that functions not only as a conveyor of information but also as a structural empowerment tool in building a women-based community economy.